1997
DOI: 10.1128/jb.179.8.2494-2502.1997
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of initiation defects of chromosome replication in Bacillus subtilis dnaA and oriC-deleted mutants by integration of a plasmid replicon into the chromosomes

Abstract: We constructed Bacillus subtilis strains in which chromosome replication initiates from the minimal replicon of a plasmid isolated from Bacillus natto, independently of oriC. Integration of the replicon in either orientation at the proA locus (115؇ on the genetic map) suppressed the temperature-sensitive phenotype caused by a mutation in dnaA, a gene required for initiation of replication from oriC. In addition, in a strain with the plasmid replicon integrated into the chromosome, we were able to delete sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(82 citation statements)
references
References 46 publications
2
79
1
Order By: Relevance
“…We used strains (27) that have oriC inactivated and that initiate replication from the dnaAindependent heterologous origin oriN (29,30). In asynchronous growth, the amount of replication initiation from oriN at 359° ( Fig.…”
Section: Inhibition Of Replication Elongation In the Head-onmentioning
confidence: 99%
“…We used strains (27) that have oriC inactivated and that initiate replication from the dnaAindependent heterologous origin oriN (29,30). In asynchronous growth, the amount of replication initiation from oriN at 359° ( Fig.…”
Section: Inhibition Of Replication Elongation In the Head-onmentioning
confidence: 99%
“…The factors required for pBS72 initiation of replication are two plasmid elements, the origin and the RepA protein, and four host-encoded replication factors, namely DnaD, DnaB, DnaI and DnaC. It is, however, surprisingly independent of the initiator proteins DnaA and PriA (so far, only orib from R6K, R1, pLS32, pAMb1 and RSF1010 have been shown to be DnaA-independent; Bernander et al, 1991;Espinosa et al, 2000;Hassan et al, 1997;Kelley & Bastia, 1992;Scherzinger et al, 1991;Tang et al, 1989). This suggests that the recruitment of the DnaD-driven cascade to the RepA/ origin complex might differ from that occurring at the DnaA/oriC and PriA/DNA complexes.…”
Section: Discussionmentioning
confidence: 99%
“…CN values presented in Table 1 were calculated from three independent measurements. Control experiments showed that the integrated plasmid replicon (pLS32) that directs chromosomal replication in the DdnaA strain (Hassan et al, 1997) does not affect pBS72 derivative CN values (not shown). CN measurement in the DpriA strain was carried out in LB with fresh transformants isolated in a poor medium.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations